Five-Tier Diagnostic Test to Reveal Conceptual Understanding of Electrical Engineering Students - Doni Setiawan; Jaelani Jaelani (Berkala Ilmiah Pendidikan Fisika, 2021)
The purpose of this research was to produce a valid five-tiered misconception diagnostic assessment product and reveal the understanding of electrical engineering students' concepts on the subject of simple electrical circuits. Assessment development consisted of defining, designing, developing, and disseminating stages. Data collection techniques were online questionnaire methods, online tests, and online interviews. Construct validity was obtained that the assessment was valid and reliable. A total of 19 questions were categorized as medium and one easy question. The analysis of the conceptual understanding test obtained results 29.98% of students who understood the concept, 31.4% did not understand the concept, 2.82% of false positive, 3.38% of false negative, and 31.12% with misconception. There were 26 kinds of student misconceptions identified. The dominant misconception identified in the concept of circuit resistance arrangement was 40.2%. Students assumed that electrons flow from high to low potential in a closed circuit with a DC voltage source. The research results in a five-tier diagnostic assessment can be used in vocational colleges in general. The results of data analysis show that the five-tier format of the assessment can reveal students' misconceptions in detail and, more specifically, distinguish students who have misconceptions from students who are false positive and false negative to reveal students who have misconceptions better. The researcher's development procedure can be used as an example for other researchers to develop a five-tier format diagnostic assessment on other basic concepts.